GENDER IN MOBILE WALLET ADOPTION BY USING UTAUT MODEL - Hermaya Ompusunggu; Meilinda Dwi Anugrah (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2021)
Mobile wallets (m-wallets) have replaced physical wallets and also replaced the use of debit and credit cards. This study aims to analyze the effect of gender on m-wallet adoption by using the UTAUT model. The research used quantitative approach with primary data was done by distributing online questionnaires. The sample was using purposive sampling and obtained 290 m-wallet users in Batam City who made a transaction through digital-based payment application during five months. The data analysis utilized SEM Partial Least Square. The results showed that performance and business expectations, social influence, and facility conditions had positive and significant effects on the intention to use m-wallets in Batam City, while gender did not have the effect in its relationship.